Akibat Hukum Kebijakan Tashih al-Quran dan Relevansinya Terhadap Upaya Pengendalian Produk Teknologi “Mushaf al-Quran Digital” di Indonesia dan Malaysia. - Hikmawati, Risma; Setiawan, Agus (UIN Fatmawati Sukarno Bengkulu, 2024)
Abstracts: The efforts to verify, standardize and regulate the distribution of the Koran in the digital era are important. The policy issued by the Malaysian State is